Smart-Charge-Pro: Innovating Energy Metering and Monitoring for Sustainable EV Stations - Dukare, Suyog I.; Bankar, Akash S.; Chobe, Pooja S.; Pardeshi, D.B.; William, P. (2023 4th International Conference on Smart Electronics and Communication (ICOSEC), 2023)
A new solution that makes use of IoT technology to optimize energy usage and cost at EV charging stations is the GPS- based net meter and cost monitoring system. The technology offers in-the-moment monitoring of energy use and cost, empowering EV users to choose their charging habits wisely. Additionally, the system may be set up to change the charging rate dependent on the cost and availability of electricity, thereby saving money for both EV owners and the owners of charging stations. Additionally, the Proposed system offers a better user interface, remote management, data analytics, customization, and scalability, making it appropriate for a variety of EV charging ecosystem applications. Due to the rising demand for EV charging infrastructure, the system's cost- saving potential, scalability, and favorable market trends towards smart cities and IoT technologies in the energy sector, the system's commercial viability is optimistic. The Internet of things, smart energy meter and cost monitoring system for EV charging stations is a useful addition to the ecosystem for EV charging, supporting environment friendly transportation and advancing the growth of smart cities.